2022
DOI: 10.3390/su142013043
|View full text |Cite
|
Sign up to set email alerts
|

System Dynamics and Graphical Interface Modeling of a Fig-Derived Micro-Producer Factory

Abstract: This study started from a fig-derived product project in the 2022–2026 Strategic Plan from Sonora, Mexico, to develop technological solutions in complex environments and provide a global panorama from the industry to the prevailing situation in Valle del Mayo. A technological solution is based on a graphical interface to support decision-making in fig supply, production and distribution in the administration process, given that the main problem has been the lack of a processing plant with a sustainable approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…From the two matrix equations described, by means of the Ackermann formula is calculated the vector of gains, where is the matrix A or internal of the system and the matrix of controllability of the system C; see Equation (6).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the two matrix equations described, by means of the Ackermann formula is calculated the vector of gains, where is the matrix A or internal of the system and the matrix of controllability of the system C; see Equation (6).…”
Section: Methodsmentioning
confidence: 99%
“…System dynamics (SD) is a tool based on simulation models that allows us to address complex situations [1] and solve specific problems. It was created in the 1950s and was called industrial dynamics, but over time it has been adapted for application to different problems [2][3][4][5][6][7][8]. SD finds its main applications in complex and undefined environments, where human decisions intervene [9].…”
Section: Introductionmentioning
confidence: 99%
“…The system's equations, grouped by type (stocks, ovens, flows, and auxiliary) are presented in Table 2. Previous studies have demonstrated that the use of level and flow diagrams generates formal visual structures based on simulators producing equations representing each one of the existing relationships in the entire supply chain [29,30]. The literature review performed by Gomes Filho et al [31] establishes a relationship between the type of supply chain and the flow of existing resources and stock accumulation.…”
Section: Constructing Stock and Flow Diagrams And Their Equationsmentioning
confidence: 99%
“…[16] Graphical user interface Design of graphical user interface with combinatorial optimization problems. [5,18,19,29] Initial contributions of system dynamics methodologyMethodologies with different applications in businesses using validation technique models.…”
Section: Author (S)mentioning
confidence: 99%
“…The method used to develop the technological solution considered the five stages described as follows [3][4][5]29]:…”
Section: System Dynamics Stagementioning
confidence: 99%